2011
DOI: 10.1111/j.1538-7836.2011.04263.x
|View full text |Cite
|
Sign up to set email alerts
|

Circulating matrix γ‐carboxyglutamate protein (MGP) species are refractory to vitamin K treatment in a new case of Keutel syndrome

Abstract: Summary. Background and objectives: Matrix c-carboxyglutamate protein (MGP), a vitamin K-dependent protein, is recognized as a potent local inhibitor of vascular calcification. Studying patients with Keutel syndrome (KS), a rare autosomal recessive disorder resulting from MGP mutations, provides an opportunity to investigate the functions of MGP. The purpose of this study was (i) to investigate the phenotype and the underlying MGP mutation of a newly identified KS patient, and (ii) to investigate MGP species a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 46 publications
1
38
0
Order By: Relevance
“…In addition, it has been shown that supplementation of high-dose vitamin K did not increase the level of cMGP in patients with Keutel syndrome. 51 Therefore, the improvement of MGP carboxylation by menaquinones may account for extrahepatic cell utilization of these K vitamins 52 for wild-type GGCX carboxylation. When the defects are caused by mutations in GGCX or MGP, menaquinones cannot ameliorate the carboxylation of MGP.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been shown that supplementation of high-dose vitamin K did not increase the level of cMGP in patients with Keutel syndrome. 51 Therefore, the improvement of MGP carboxylation by menaquinones may account for extrahepatic cell utilization of these K vitamins 52 for wild-type GGCX carboxylation. When the defects are caused by mutations in GGCX or MGP, menaquinones cannot ameliorate the carboxylation of MGP.…”
Section: Discussionmentioning
confidence: 99%
“…43 Similarly, cranial CT scan and multislice CT scanning of the coronary arteries revealed no calcification in a 21-year-old men with genetically confirmed Keutel syndrome. 44 Unfortunately, their PWVs were not reported. One hypothesis that could be in line with our results and the absence of calcifications in tomography in Keutel patients is that a high level of inactive MGP leads to an increase in the number, or in the size, of calcifications, but sufficiently scattered in the vessels not to be detectable by tomography.…”
mentioning
confidence: 99%
“…However, literature review revealed only 10 patients with molecular diagnosis [Munroe et al, 1999;Hur et al, 2005;Cranenburg et al, 2011;Weaver et al, 2014;Tüysüz et al, 2015;Bayramoğlu et al, 2016]. These patients shared 7 distinct pathogenic variants: 3 were donator or acceptor splice site type (IVS1-2A>G/c.62-2A>G; IVS2+1G>A; IVS1+1G>A/c.61+1G>A), 3 were deletion variants [1 missense (c.113T>A), 1 nonsense (c.79G>T; p.Glu27X), and 1 frameshift (c.69delG)], and 1 was a partial deletion of exon 4.…”
Section: Discussionmentioning
confidence: 99%